Spexin Adipokinin and TRPM2 ION Channel in Lung Cancer Use as a Bıomarker in Hıstopathologic Diagnosis - Aydin, Siyami (Asian Pacific Organization for Cancer Prevention, 2025)
Background: Lung cancer is the most common cancer with the highest mortality rate. Spexin peptide acts as a potential regulatory factor in glucose and energy metabolism in this cancer type. It has been reported that TRPM2 ion channel is formed by oxidative stress and stimulates Ca2++ influx in cancer patients. Objective: In our study, we aimed to immunohistochemically determine the activity levels of Spexin peptide and TRPM2 ion channels in lung cancer patients and to differentiate their levels according to cancer type. Methods: To determine the effects of these peptides and ion channels in lung cancer, 30 cases with lung cancer and 30 randomised control groups were formed. The activity levels of Spexin peptide and TRPM2 ion channels in different types of lung cancer and non-cancerous groups were compared. Results: The study examined lung cancer subtypes (Adeno Ca, SCC, and Small Cell Ca) and a control group. Spexin and TRPM2 levels were significantly higher in Adeno Ca and SCC compared to controls and Small Cell Ca. Small Cell Ca showed no significant difference from controls. No differences were found between Adeno Ca and SCC.Conclusion: Immunoreactivity levels of these markers were found to be higher in adenocarcinoma and squamous cell lung cancer tissues than in small cell cancer and non-cancerous tissues. In conclusion, spexin and TRPM2 ion channel levels can be evaluated as a marker in adenocarcinoma and squamous cell lung cancer. © (2025), (Asian Pacific Organization for Cancer Prevention). All rights reserved.
Keywords: Lung cancer; Spexin peptide and TRPM2 ion channel iminoreactivity